KREDIT KENDARAAN BERMOTOR KEPADA NASABAH BRI (STUDI PADA BANK RAKYAT INDONESIA CABANG GAJAH MADA MEDAN) - RINA ULI (University of North Sumatera, 2013)
Abstrak : The economics of Indonesia is developed rapidly especially in banking. More of bank’s products that developed and there are any bank business process. The credit supplied by bank and required by customer is a consumptive credit, i.e. the credit of motor vehicle. The law has an important role in the form of regulation in order to assure the interest of bank or customer. So, there is a problem formulation in respond how the requirements and procedure in supply the motor vehicle credit at PT BRI Branch of Gajah Mada Medan, what factors cause the costumer in motor vehicle is in problem ang how the settlement of the motor vehicle credit at PT BRI Branch of Gajah Mada Medan. Thye regulation about type of motor vehicle credit aims to minimize the bad credit by enforcement of the rule and the understanding of customer about the motor vehicle credit by bank. Keywords : banking, Consumptive Credit, Motor Vehicle Credit